Beispiel Nr: 01
$ \text{Gegeben:}\\\text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\\text{Mantelfläche} \qquad M \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Grundfläche} \qquad G \qquad [m^{2}] \\ \\ G = O-M\\ \textbf{Gegeben:} \\ O=5m^{2} \qquad M=6m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ G = O-M \\ M=6m^{2}\\ O=5m^{2}\\ G =5m^{2}-6m^{2}\\\ G=-1m^{2} \\ \small \begin{array}{|l|} \hline O=\\ \hline 5 m^2 \\ \hline 500 dm^2 \\ \hline 5\cdot 10^{4} cm^2 \\ \hline 5\cdot 10^{6} mm^2 \\ \hline 0,05 a \\ \hline 0,0005 ha \\ \hline 5\cdot 10^{-6} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline M=\\ \hline 6 m^2 \\ \hline 600 dm^2 \\ \hline 6\cdot 10^{4} cm^2 \\ \hline 6\cdot 10^{6} mm^2 \\ \hline 0,06 a \\ \hline 0,0006 ha \\ \hline 6\cdot 10^{-6} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline G=\\ \hline -1 m^2 \\ \hline -100 dm^2 \\ \hline -10^{4} cm^2 \\ \hline -10^{6} mm^2 \\ \hline -0,01 a \\ \hline -0,0001 ha \\ \hline -10^{-6} km^2 \\ \hline \end{array}\\$